Thermal properties and morphology of ethylene vinyl acetate/ epoxidized natural rubber/ halloysite nanotube (EVA/ENR-50/HNTs) nanocomposites. - Mohamad, Zurina (2012)
The effects of sepiolite nanofiller addition and irradiation modification on the tensile properties of epoxidized natural rubber (ENR-50)/ehylene vinyl acetate (EVA)/Sepiolite nanocomposites were investigated. The ENR-50/EVA/Sepiolite was blended by mixing in a Brabender Plastigraph at 120 °C. The samples were irradiated by using electron beam at a dose range of 50 to 200 kGy. The effect on the tensile properties and morphology were investigated as a function of sepiolite content and irradiation dose. Electron beam radiation produced an irradiation-induced crosslinking and further enhanced mechanical properties of the nanocomposites. The tensile properties of irradiated ENR-50/EVA blend were improved by the addition of sepiolite at 4 phr.